Diversify or not? The link between global sourcing of ICT goods and firm performance - Alexander Schiersch; Irene Bertschek; Thomas Niebel (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
Our paper contributes to the discussion about Europe's digital sovereignty. We analyze the relationship between firm performance and the diversification of sourcing countries for imported ICT goods. The analysis is based on administrative data for 3888 German manufacturing firms that imported ICT goods in the years 2010 and 2014. We find that firms that diversify the sourcing of ICT goods across multiple countries perform better than similar firms with a less diversified sourcing structure. This result holds for value added as well as for gross operational surplus as performance measures and for two different indicators of diversification.
Keywords: F14; F23; L14; L23; D24; 330; ICT goods imports; global sourcing; digital sovereignty; firm performance